Take a Ride on Credibility: The Role of Brand Personality in Users’ Loyalty to Virtual Brands in the Sharing Economy - Moreno, Lucas; Demo, Gisela; Rocha, Thelma Valéria; Scussel, Fernanda (Internext, 2021)
Objective: Although the sharing economy is a global phenomenon, being a path to create international brands with a worldwide customer reach, the relationship between virtual brands and users’ in this new sector remains underexplored, leading us to investigate the relation between brand personality and users’ loyalty to virtual brands. Method: Survey with 580 users of ride apps, using structural equation modeling to test the prediction of brand personality on user’s loyalty. Results: The present research depicts the intangible aspects of the relationship between users and brands in the digital environment, revealing the personality traits of virtual brands and the impact on customer loyalty in the context of the sharing economy. Credibility and audacity are the most prominent characteristics of virtual brands, being credibility, reflecting the users’ trust in the brand, the main driver of loyalty. Contributions: These findings contribute to the relationship marketing body of knowledge; in a sense, it provides information about how customers relate to their favorite virtual brands and indicates an antecedent of relationship marketing. Customer brand relationship studies also benefit from our results since we suggest important factors that enable positive associations about a brand in consumers’ minds. Relevance/Originality: This study represents a seminal step in investigating the relational aspects of the interaction between users and virtual brands in the sharing economy, which has brought the need to rethink brand management and brand positioning in the context of virtual brands.